2015
DOI: 10.1088/0963-0252/24/5/055016
|View full text |Cite
|
Sign up to set email alerts
|

Gradual increase in secondary ionization coefficientγand charge accumulation on a dielectric electrode during DBD with repeated breakdown

Abstract: We have investigated the effect of the surface roughness of a dielectric electrode for dielectric barrier discharge (DBD). We prepared three alumina plates made from the same material with different surface roughnesses for use as electrodes. During the repeated breakdown from the first breakdown to the stationary state, we observed gradual increases in the secondary ionization coefficient and the charge accumulated on the alumina electrodes under the application of a sinusoidal voltage in argon up to a pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…In addition, the charges accumulation on the wall may also provide additional seed electrons for the discharge ignition, which plays an important role in the lower ignition voltage and the formation of the Townsend discharge in DBD. [42] However, there is lack of enough consistent information concerning the effect of surface charges on the discharge ignition and the ionization wave propagation inside the capillary. A future work on the measurement of the surface charges inside capillary is required to address this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the charges accumulation on the wall may also provide additional seed electrons for the discharge ignition, which plays an important role in the lower ignition voltage and the formation of the Townsend discharge in DBD. [42] However, there is lack of enough consistent information concerning the effect of surface charges on the discharge ignition and the ionization wave propagation inside the capillary. A future work on the measurement of the surface charges inside capillary is required to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…When the voltage polarity is reversed, the surface charges will enhance the electric field. In addition, the charges accumulation on the wall may also provide additional seed electrons for the discharge ignition, which plays an important role in the lower ignition voltage and the formation of the Townsend discharge in DBD . However, there is lack of enough consistent information concerning the effect of surface charges on the discharge ignition and the ionization wave propagation inside the capillary.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible factor is the surface charge accumulated on the dielectric surface, which is largely dependent on the types of dielectric material . Li et al reported that the desorption of the trapped electrons on the dielectric surface can provide seed electrons for the diffuse discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible factor is the surface charge accumulated on the dielectric surface, which is largely dependent on the types of dielectric material. [30][31][32][33][34][35] Li et al [31] reported that the desorption of the trapped electrons on the dielectric surface can provide seed electrons for the diffuse discharge. Radu [36] found that the trapped charge on the dielectric surface reduces the propagation velocity of the discharge across the gap and increases the width of the discharge channel.…”
Section: Figure 16mentioning
confidence: 99%
“…From our experience [23], as well as from the results in the literature [24][25][26], the electron emissivity of the cathode (electron yield) may increase/decrease with a large number of repeated light illuminations or particle irradiations. Namely, the adsorption/desorption of gases and impurities, roughening or smoothing of the cathode surface due to sputtering, cleaning, aging, etc.…”
Section: Electron Avalanche Number Distributions When the Electron Em...mentioning
confidence: 99%